Assessment of shoulder joint and muscle characteristics side-asymmetry in professional padel players - Viera, H. L. S.; Leite-Nunes, T. D.; Gidiel-Machado, L.; Laporta, L. I.; Royes, L. F. F.; Forgiarini Saccol, M.; Lanferdini, F. J. (Sports Biomechanics, 2025)
Padel is a worldwide racket sport that is growing each year. The unilateral upper limb repetitive movements of this sport may lead to shoulder structural and functional adaptations, which may alter muscle mechanics, however evidence is limited. We aimed to investigate if there is morphological, mechanical and functional shoulder symmetry between upper limbs of professional padel players. Fourthteen (7m and 7f) professional Brazilian padel players were evaluated at supraspinatus muscle thickness (MT), stiffness, shoulder rotation range of motion (ROM), shoulder internal and external rotation peak torques and their ratios (ER/IR) and fatigue index torque. Subsequently, were compared all variables between dominant and non-dominant sides (a = 0.05). Total work, IR and ER absolute and normalised torque were higher in the dominant limb (p < 0.05). Moreover, 78% and 64% of the athletes presented reduced ER/IR peak torque ratio values in the dominant and non-dominant upper limb, respectively. No differences in supraspinatus MT, stiffness and shoulder ROM were found. Our study found that Brazilian professional padel players have asymmetrical shoulder ER/IR peak torques ratio. Therefore, it`s recommended for padel players to strengthen the ER of the dominant shoulder and both IR and ER of the non-dominant shoulder to address side-asymmetry and reduced ER peak torques.